PENGARUH INFLASI DAN PERTUMBUHAN PENDUDUK TERHADAP PERTUMBUHAN EKONOMI KOTA LHOKSEUMAWE - Fauzan Fauzan; Mahmuddin Mahmuddin (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2019)
This study aims to know to know whether inflation and population growth affect Lhokseumawe city economic growth. Data used is time series data from year 2006-2016. The method used for data analysis is multiple linear regression. The result of research is Based on the result of the research, it is found that Inflation influence to Economic Growth. Based on the results of the research, it is found that population growth has no effect on economic growth. that inflation and population growth significantly influence the variable of economic growth. Thus this regression model can explain inflation and population growth together affect economic growth.